Hubungan Pola Asuh Otoriter terhadap Struktur Kepribadian Manusia dalam Perspektif Sigmund Freud - Lubis, Muhammad Alridho; Ariyati, Ika; Harahap, Nur Hasanah; Pierda, Kheylyla Adha; Nopitri, Harti Zakia; Finanjani, Syakila (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
The order of human life started from the birth of a parenting style given by parents. Parenting plays a role in education and teaching to control and regulate children’s lives during the span of their development. Authoritarian parenting is part of the three types of parenting styles proposed by Hurlock. The characteristics of this form of authoritarian parenting are strict controls, strict discipline, and a lack of freedom in making decisions for children. Judging from the form of aspects arising from authoritarian parenting tend to lead to negative personality forms. Therefore, the relationship between parenting in the formation of one’s personality is very close. Parenting is the thing that underlies the formation of a person’s character and personality for the future. The good or bad of a person’s personality can be seen from the upbringing received from both parents and the environment in which the individual grows and develops.